Sistem Informasi Manajemen Organisasi Perannya dalam Pengambilan Keputusan dan Pemecahan Masalah - Adisel Adisel; Robeet Thadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is that management information systems provide accurate and timely information needed to facilitate the decision-making and problem-solving processes that enable the implementation of planning, control and operational functions to run effectively. The approach in scientific writing uses a qualitative descriptive method. The results of this study indicate that the development and management of MIS in an organization is able to trigger decisions that are not only fast and accurate but will also be in line with the best practices in the organization effectively and efficiently. Information has become an important source for managing modern organizations. Keywords: Management Information Systems (MIS), Decision Making and Problem Solving